Polymer-oxide gradient composite electrolyte and method of making same
Patent Information
- Application Number
- CN202611243276.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-27
AI Technical Summary
第一,低温性能差
本发明通过含硫杂环聚合物基质、梯度分布氧化物骨架、混合锂盐及低熔点离子液体添加剂的协同组合,构建了兼具高离子电导率、低界面阻抗和优异热稳定性的复合电解质体系,其核心在于:利用含硫杂环单体中硫原子的孤对电子与锂离子形成弱配位作用以降低离子迁移能垒,结合低熔点离子液体在低温下维持的液相离子传输通道,使得电解质在-40℃下的离子电导率不低于1.0×10-4S/cm,从根本上解决了传统聚合物电解质低温链段冻结导致离子传导失效的技术难题;通过在电解质厚度方向建立从正极侧高氧化物含量(40~60wt%)到负极侧低氧化物含量(10~20wt%)的梯度分布,使正极侧获得足够的机械强度和热稳定性以抑制锂枝晶穿刺并承受较高热负荷,同时确保负极侧保持充足的聚合物柔性以实现与锂金属负极的紧密界面接触,显著降低了界面阻抗,配合多级孔道氧化物骨架中纳米级(50~200nm)与微米级(1~5μm)颗粒的合理级配所形成的连续快速离子传导网络,使得固态电池在5C高倍率下容量保持率不低于80%,有效改善了固态电池的倍率性能;同时,高含量氧化物骨架(热分解温度>500℃)与阻燃离子液体(分解温度>400℃)的协同作用,结合交联聚合物三维网络结构对高温下聚合物链段运动的抑制,使电解质的热失控起始温度提升至220℃以上,在60℃高温下1C循环500次后容量保持率不低于90%,攻克了现有固态电解质高温热稳定性不足的瓶颈;此外,本发明采用先涂覆-烧结形成氧化物骨架再浸渍前驱体溶液并光引发聚合的非原位复合工艺,避免了原位聚合中单体与电极直接接触引发的界面副反应,工艺条件温和、与现有电池产线兼容性好,具有广阔的产业化应用前景。
Smart Images

Figure CN122992151A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid-state battery technology, and in particular to a polymer-oxide gradient composite electrolyte and its preparation method. Background Technology
[0002] With the rapid development of electric vehicles, large-scale energy storage systems, and portable electronic devices, the demand for rechargeable batteries with high energy density, high safety, and long cycle life is becoming increasingly urgent. Traditional lithium-ion batteries use organic liquid electrolytes, which pose safety hazards such as flammability, explosion, and leakage, making it difficult to meet increasingly stringent safety requirements. Solid-state batteries, which use solid electrolytes instead of liquid electrolytes, fundamentally solve the safety issues and are considered an important development direction for next-generation high-performance batteries.
[0003] Solid-state electrolytes are the core component of solid-state batteries, and are mainly classified into three categories: inorganic solid-state electrolytes, polymer solid-state electrolytes, and composite solid-state electrolytes. Inorganic solid-state electrolytes (such as oxide-type and sulfide-type electrolytes) have high ionic conductivity (up to 10⁻⁶). -3 ~10 -2 While possessing excellent thermal stability (S / cm), polymer solid electrolytes suffer from poor contact with the electrode interface, difficult processing and molding, and high brittleness. Polymer solid electrolytes (such as polyethylene oxide (PEO), polyacrylonitrile (PAN), and polyvinylidene fluoride (PVDF)) exhibit good flexibility and interfacial compatibility, and are simple to process, but suffer from low room-temperature ionic conductivity (typically 10). -6 ~10 -5 (S / cm), insufficient thermal stability, and narrow electrochemical window.
[0004] To combine the advantages of inorganic and polymer electrolytes, researchers have proposed a composite solid-state electrolyte approach, which involves dispersing inorganic oxide particles within a polymer matrix to simultaneously achieve high ionic conductivity and good interfacial contact properties. However, existing composite solid-state electrolytes still face the following three core technological challenges: First, poor low-temperature performance. The ion conduction of traditional polymer electrolytes (such as PEO-based electrolytes) is highly dependent on the movement of polymer chain segments. Below -20°C, the movement of polymer chain segments is frozen, and the ionic conductivity drops sharply to 10. -7 When the S / cm ratio is below a certain value, solid-state batteries cannot function properly in low-temperature environments. This problem severely restricts the application of solid-state batteries in extremely cold regions and special low-temperature environments.
[0005] Second, rate performance is limited. In composite solid-state electrolytes, numerous interfaces exist between inorganic particles and the polymer matrix, resulting in high interfacial impedance that hinders rapid lithium-ion transport. At high current densities (e.g., above 5C), battery capacity decays significantly, failing to meet fast-charging requirements. Interfacial impedance has become a bottleneck restricting improvements in the rate performance of solid-state batteries.
[0006] Third, insufficient high-temperature thermal stability. Most polymer matrices (such as PEO, PAN, etc.) have low thermal decomposition temperatures (approximately 150~200℃), making them prone to thermal runaway at high temperatures. Furthermore, the difference in thermal expansion coefficients between polymer and oxide particles can lead to interfacial delamination and structural damage at high temperatures, further deteriorating battery performance. Existing composite solid electrolytes are insufficient to meet the requirements for long-term stable operation in environments above 60℃.
[0007] To address the aforementioned issues, researchers have attempted improvements through the following approaches: adding plasticizers or ionic liquids to enhance low-temperature conductivity; optimizing the type and content of inorganic fillers to improve interfacial properties; and employing cross-linked network structures to improve the heat resistance of the polymer matrix. However, these improvement schemes typically only optimize a single performance indicator and struggle to simultaneously meet the comprehensive requirements of low-temperature performance, rate performance, and high-temperature stability. Furthermore, the oxide particles in existing composite electrolytes are usually uniformly distributed, making it impossible to differentiate designs for the different functional requirements of the positive and negative electrode sides.
[0008] Therefore, developing a composite solid electrolyte that can simultaneously solve the three major technical challenges of poor low-temperature performance, limited rate performance, and insufficient high-temperature thermal stability has significant theoretical and practical application value. Summary of the Invention
[0009] In order to overcome the above-mentioned defects of the prior art, the present invention provides a polymer-oxide gradient composite electrolyte and its preparation method to solve the problems existing in the background art.
[0010] The present invention provides the following technical solution: In a first aspect, the present invention provides a polymer-oxide gradient composite electrolyte, comprising: (a) Polymer matrix The polymer matrix is formed by photo-initiated polymerization of sulfur-containing heterocyclic monomers, comonomers and crosslinking agents.
[0011] The sulfur-containing heterocyclic monomer is a monomer containing a sulfur heterocyclic structure that can be photoinitiated to form a polymer. For example, 3,4-ethylenedioxythiophene derivatives (such as ethyl 3,4-ethylenedioxythiophene-3-carboxylate) or thiophene-2-carboxylic acid ester derivatives can be selected. The sulfur atoms of the sulfur-containing heterocyclic monomer have lone pairs of electrons, which can form weak coordination interactions with lithium ions, lowering the energy barrier for lithium ion hopping and migration between polymer segments, thereby maintaining a high ion migration rate even at low temperatures. The content of this sulfur-containing heterocyclic monomer in the polymer matrix can, for example, be 60-80 wt%.
[0012] The comonomer is used to adjust the glass transition temperature and mechanical properties of the polymer matrix. For example, N-vinylcaprolactam or 2-vinylpyridine can be selected, and the content in the polymer matrix can be 15~30wt% for example.
[0013] Crosslinking agents are used to construct the three-dimensional network structure of polymers, thereby improving the thermal stability and mechanical strength of polymers. Tris(2-methacryloyloxyethyl) isocyanurate or triallyl isocyanurate can be selected by example, and the content in the polymer matrix can be 2 to 5 wt% by example.
[0014] (ii) Oxide skeleton The oxide framework consists of hierarchical porous oxide particles, forming a gradient distribution from the positive electrode side to the negative electrode side along the electrolyte thickness direction. The oxide content on the positive electrode side (i.e., the side facing the positive electrode during use) is 40-60 wt%, while the oxide content on the negative electrode side (i.e., the side facing the negative electrode during use) is 10-20 wt%. The principle behind this gradient distribution design is that the positive electrode side requires a higher oxide content to provide sufficient mechanical strength to suppress lithium dendrite penetration and high thermal stability to withstand the high thermal load on the positive electrode side. At the same time, the high oxide content helps to construct continuous fast ion conduction channels. Conversely, the negative electrode side requires a lower oxide content to maintain a high polymer ratio, thereby ensuring a smooth interface contact with the lithium metal negative electrode and reducing interfacial impedance.
[0015] The hierarchical porous oxide particles comprise a mixture of nanoscale particles (exemplary particle size 50–200 nm) and microscale particles (exemplary particle size 1–5 μm). The nanoscale particles primarily fill the gaps between the microscale particles, forming a multi-scale porous structure, which facilitates thorough impregnation of the precursor solution and the construction of ion transport channels. The oxide particles can, exemplary examples, be aluminum-doped titanium dioxide (Al-TiO2) or lanthanum-doped zirconium oxide (La-ZrO2), as the doping elements enhance the ionic conductivity of the oxide particles themselves. Organic molecules are grafted onto the surface of oxide particles, wherein the organic molecules contain groups compatible with the polymer matrix (such as mercapto, amino, isocyanate groups, etc.) and groups that can bond to the oxide surface (such as silanoxy groups), selected from 3-mercaptopropyltrimethoxysilane, 3-aminopropyltriethoxysilane or 3-isocyanopropyltriethoxysilane, forming an organic modification layer on the surface of the oxide particles. This modification layer can reduce the interfacial tension between the oxide and the polymer, improve the interfacial bonding force between the two, and reduce the interfacial impedance.
[0016] (iii) Electrolyte salts The electrolyte salt is dispersed in a polymer matrix, providing charge carriers for lithium-ion transport. The electrolyte salt comprises a mixture of a first lithium salt and a second lithium salt. The first lithium salt is, exemplarily, lithium bis(oxalate)tetrafluoroborate (LiBF2(C2O4)), and the second lithium salt is, exemplarily, lithium difluorophosphate (LiPO2F2). The mass ratio of the first lithium salt to the second lithium salt is, exemplarily, 3:1 to 5:1. The synergistic effect of the two lithium salts is manifested in the following ways: lithium bis(oxalate)tetrafluoroborate has a high thermal decomposition temperature (>300℃), enabling it to remain stable at high temperatures; lithium difluorophosphate can participate in the formation of a stable SEI film on the negative electrode surface, reducing interfacial impedance; both exhibit high dissociation at low temperatures, contributing to maintaining low-temperature ionic conductivity.
[0017] (iv) Low-temperature additives The low-temperature additive is a low-melting-point ionic liquid, exemplary selected from 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([EMIM][TFSI]) or 1-butyl-1-methylpyrrolidine bis(fluorosulfonyl)imide ([Py14][FSI]), with melting points of approximately -15°C and -18°C respectively, and remaining liquid at -40°C. The content of the low-temperature additive in the electrolyte is exemplary 5~15 wt%. The ionic liquid acts as a plasticizer in the polymer matrix, increasing the free volume of polymer chain segments and promoting chain segment movement, thereby maintaining ion migration ability at low temperatures. Simultaneously, the ionic liquid has good compatibility with sulfur-containing heterocyclic polymers, preventing macroscopic phase separation and ensuring the structural homogeneity of the composite electrolyte.
[0018] In the above technical solution, the polymer matrix and the oxide framework form an interpenetrating network structure: the polymer phase fills the pores between oxide particles and coats the surface of the oxide particles, forming a continuous phase; the oxide particles contact each other to form a continuous framework. The dual continuous phase structure ensures that lithium ions can be transported both through the chain segment movement in the polymer phase and through the fast channels in the oxide framework, realizing a multidimensional ion conduction pathway.
[0019] In the above technical solution, the ionic conductivity of the polymer-oxide gradient composite electrolyte at -40℃ is exemplary not less than 1.0 × 10⁻⁶. -4 The ionic conductivity at 25°C is, by example, not less than 2.0 × 10⁻⁶ S / cm. -3 S / cm, thermal runaway initiation temperature is exemplary not less than 220°C, and lithium-ion transference number is exemplary not less than 0.6.
[0020] Secondly, the present invention provides a method for preparing a polymer-oxide gradient composite electrolyte, comprising the following steps: Step 1: Disperse oxide particles in a solvent (such as isopropanol), add a binder (such as polyvinyl butyral), and ultrasonically disperse until uniform, preparing coating slurries with different oxide contents. On a substrate (such as a glass substrate), sequentially coat slurries with different oxide contents (e.g., first coat a high-content slurry, then coat a low-content slurry), performing preliminary drying after each coating to form a wet film with an oxide content gradient distribution along the thickness direction. For example, the coating speed is 0.1~10 cm / s, and 2~4 coatings can be applied, with preliminary drying at 80~100℃ for 5~15 minutes after each coating. By adjusting the oxide concentration and coating thickness of each slurry layer, the gradient distribution curve can be precisely controlled.
[0021] Step 2: The gradient wet film obtained in Step 1 is dried and then sintered at 250~350℃ to remove the binder and form neck connections between oxide particles, resulting in a multi-level porous oxide framework with a gradient distribution. For example, the sintering uses a programmed temperature rise rate of 1~2℃ / min and a holding time of 2~4 hours. This low-temperature sintering process avoids over-sintering of oxide particles and pore collapse caused by high temperatures, preserving the multi-level porous structure.
[0022] Step 3: Dissolve the sulfur-containing heterocyclic monomer, comonomer, crosslinking agent, first lithium salt, and second lithium salt in an organic solvent, add a low-temperature additive, and stir until homogeneous to obtain a precursor solution. For example, the organic solvent may be N-methylpyrrolidone or γ-butyrolactone, and the amount used should be sufficient to fully dissolve the components and have a suitable impregnation viscosity.
[0023] Step 4: Immerse the hierarchical porous oxide framework obtained in Step 2 in the precursor solution obtained in Step 3, ensuring the precursor solution fully fills the pores of the oxide framework. After removal, irradiate with ultraviolet light under an inert atmosphere (such as argon or nitrogen) to initiate monomer polymerization, forming a polymer-oxide composite structure. For example, the ultraviolet light wavelength is 365 nm, and the light intensity is 10~50 mW / cm². 2 The irradiation time is 5-30 minutes. The advantages of photo-initiated polymerization over thermally initiated polymerization are: low temperature conditions can avoid side reactions that may occur during high-temperature initiation polymerization (such as electrolyte salt decomposition, monomer thermal polymerization, etc.), and the polymerization rate is uniform and controllable.
[0024] Step 5: Vacuum dry the composite structure obtained in Step 4 to remove residual organic solvents, obtaining a polymer-oxide gradient composite electrolyte. For example, the drying temperature is 40~60℃, and the drying time is 8~24 hours.
[0025] In the above preparation method, the process route of first forming an oxide skeleton and then impregnating the precursor solution and polymerizing in steps 1 to 2 (i.e., the "non-in-situ" composite route) has the following advantages over the "in-situ" mixing route of directly dispersing oxide particles in monomer solution and then casting and polymerizing: it can precisely control the gradient distribution morphology and pore structure of oxide particles, avoid uneven distribution caused by particle sedimentation, and avoid the interference of oxide particles on the polymerization reaction during the polymerization process.
[0026] Thirdly, the present invention provides a solid-state battery comprising the above-described polymer-oxide gradient composite electrolyte, as well as a positive electrode and a negative electrode.
[0027] The positive electrode contains a positive electrode active material, which is exemplary selected from high-nickel ternary materials (such as LiNi). 0.8 Co 0.1 Mn 0.1 The cathode may contain O2 (NCM811), lithium cobalt oxide (LiCoO2), or lithium iron phosphate (LiFePO4). It may also contain conductive agents (such as SuperP) and binders (such as PVDF).
[0028] The negative electrode is metallic lithium, lithium alloy, or silicon-carbon composite material.
[0029] For example, an interface modification layer composed of lithium lanthanum titanium oxide (LLTO) or lithium lanthanum zirconium oxide (LLZO) nanoparticles is provided between the positive electrode and the electrolyte to improve the solid-solid contact between the positive electrode and the electrolyte. An artificial SEI layer composed of lithium sulfide (Li2S), lithium nitride (Li3N), or lithium fluoride (LiF) is provided between the negative electrode and the electrolyte to suppress lithium dendrite growth and side reactions.
[0030] This solid-state battery can operate in a temperature range of -40°C to 80°C, and its capacity retention rate is, for example, no less than 80% at a 5C rate. For example, after 200 cycles at 0.5C at -30°C, the capacity retention rate is no less than 85%, and after 500 cycles at 1C at 60°C, the capacity retention rate is no less than 90%.
[0031] Fourthly, the present invention provides a method for preparing a solid-state battery, comprising the following steps: Step 1: Mix the positive electrode active material, conductive agent, and binder in a certain proportion (e.g., mass ratio 90:5:5), coat it onto the positive electrode current collector (e.g., aluminum foil), and dry it to obtain the positive electrode sheet; Step 2: Mix the negative electrode active material, conductive agent, and binder in a certain proportion, coat the mixture onto the negative electrode current collector (such as copper foil), and dry it to obtain the negative electrode sheet; Step 3: Place the polymer-oxide gradient composite electrolyte prepared by the above method between the positive electrode and the negative electrode; Step 4: Hot-press at 80~100℃ for 0.5~2 hours, with an exemplary pressure of 0.5~2MPa, to ensure tight bonding between the electrolyte and the positive and negative electrode interfaces; Step 5: Encapsulate the hot-pressed structure to obtain a solid-state battery.
[0032] The technical effects and advantages of this invention are as follows: This invention constructs a composite electrolyte system with high ionic conductivity, low interfacial impedance, and excellent thermal stability through the synergistic combination of a sulfur-containing heterocyclic polymer matrix, a gradient-distributed oxide framework, mixed lithium salts, and low-melting-point ionic liquid additives. The core of this system lies in utilizing the lone pair electrons of sulfur atoms in the sulfur-containing heterocyclic monomer to form weak coordination with lithium ions, thereby lowering the ion migration barrier. Combined with the liquid-phase ion transport channels maintained by the low-melting-point ionic liquid at low temperatures, the ionic conductivity of the electrolyte at -40°C is not less than 1.0 × 10⁻⁶. -4The S / cm ratio fundamentally solves the technical problem of ion conduction failure caused by low-temperature chain segment freezing in traditional polymer electrolytes. By establishing a gradient distribution along the electrolyte thickness from high oxide content (40~60wt%) on the positive electrode side to low oxide content (10~20wt%) on the negative electrode side, the positive electrode side obtains sufficient mechanical strength and thermal stability to suppress lithium dendrite puncture and withstand high thermal loads, while ensuring sufficient polymer flexibility on the negative electrode side to achieve tight interfacial contact with the lithium metal negative electrode. This significantly reduces interfacial impedance. Combined with the continuous and rapid ion conduction network formed by the reasonable gradation of nanoscale (50~200nm) and microscale (1~5μm) particles in the multi-level porous oxide framework, the solid-state battery maintains a capacity retention of no less than 80% at a high rate of 5C, effectively... This invention improves the rate performance of solid-state batteries. Simultaneously, the synergistic effect of a high-content oxide skeleton (thermal decomposition temperature > 500℃) and flame-retardant ionic liquid (decomposition temperature > 400℃), combined with the suppression of polymer chain movement at high temperatures by the three-dimensional network structure of cross-linked polymers, raises the thermal runaway initiation temperature of the electrolyte to over 220℃. After 500 cycles at 60℃ using 1C, the capacity retention rate is no less than 90%, overcoming the bottleneck of insufficient high-temperature thermal stability in existing solid-state electrolytes. Furthermore, this invention employs a non-in-situ composite process: first coating and sintering to form an oxide skeleton, then impregnating it with a precursor solution and photo-initiating polymerization. This avoids interfacial side reactions caused by direct contact between monomers and electrodes in in-situ polymerization. The process conditions are mild, and it has good compatibility with existing battery production lines, showing broad prospects for industrial application. Attached Figure Description
[0033] Figure 1 The flowchart illustrates the preparation process of the polymer-oxide gradient composite electrolyte provided in this embodiment of the invention.
[0034] Figure 2 This is a schematic diagram of the test results of the polymer-oxide gradient composite electrolyte provided in an embodiment of the present invention. Detailed Implementation
[0035] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described below in conjunction with the accompanying drawings and specific embodiments. However, it should be understood that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Experimental methods not specifically described in the embodiments are generally performed under conventional conditions in the art or according to the manufacturer's recommendations. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0036] Example 1: Preparation of polymer-oxide gradient composite electrolyte This embodiment provides a method for preparing a polymer-oxide gradient composite electrolyte, the specific steps of which are as follows.
[0037] 1.1 Preparation of oxide coating slurry (1) Preparation of positive electrode side slurry (high oxide content): Weigh 0.2g of nano-aluminum-doped titanium dioxide (Al-TiO2, average particle size 50nm) and 0.3g of micron-doped lanthanum-doped zirconium oxide (La-ZrO2, average particle size 2μm), disperse them in 10mL of isopropanol, add 0.1g of polyvinyl butyral (PVB) as a binder, and ultrasonically disperse for 30 minutes to obtain the positive electrode side coating slurry (slurry A).
[0038] (2) Preparation of negative electrode side slurry (low oxide content): Weigh 0.05 g of nano-aluminum-doped titanium dioxide (Al-TiO2, average particle size 50 nm) and 0.05 g of micron-doped lanthanum-doped zirconium oxide (La-ZrO2, average particle size 2 μm), disperse them in 10 mL of isopropanol, add 0.1 g of polyvinyl butyral (PVB) as a binder, and ultrasonically disperse for 30 minutes to obtain the negative electrode side coating slurry (slurry C).
[0039] (3) Preparation of intermediate transition slurry: The positive electrode slurry and the negative electrode slurry are mixed at a mass ratio of 3:1 and stirred evenly to obtain an intermediate transition slurry (slurry B). The oxide content of this slurry is between that of slurry A and slurry C, which is used to achieve a gradient transition in oxide content.
[0040] 1.2 Preparation of Gradient Wet Film The coating is applied to the glass substrate in the following order: (1) First coating: The slurry A (high oxide content) is uniformly coated on the glass substrate at a coating speed of 2 cm / s and the coating thickness is controlled to be about 10 μm (dry thickness). It is then dried at 80°C for 10 minutes. (2) Second layer coating: Apply slurry B (intermediate transition) to the dried surface of the first layer at a coating speed of 2 cm / s and control the coating thickness to about 10 μm (dry thickness). Dry at 80°C for 10 minutes. (3) Third layer coating: Apply slurry C (low oxide content) to the dried second layer surface at a coating speed of 2 cm / s and control the coating thickness to about 10 μm (dry thickness). Dry at 80°C for 10 minutes.
[0041] After the above three coating steps, a wet film with a total thickness of about 30 μm (dry state) is formed on the glass substrate, and the oxide content decreases in a gradient from the bottom layer (positive electrode side) to the surface layer (negative electrode side) along the thickness direction.
[0042] 1.3 Preparation of Gradient Oxide Framework The aforementioned gradient wet film was placed in a muffle furnace and heated to 300°C at a rate of 1°C / min, and then sintered at 300°C for 3 hours. During sintering, the PVB binder was completely decomposed and removed, and neck connections were formed between the oxide particles, resulting in a multi-level porous oxide skeleton with a gradient distribution. In this skeleton, the oxide content of the bottom layer (original slurry layer A) is approximately 50 wt%, the oxide content of the middle layer (original slurry layer B) is approximately 35 wt%, and the oxide content of the surface layer (original slurry layer C) is approximately 15 wt%, forming a gradient decreasing distribution from bottom to top.
[0043] 1.4 Preparation of precursor solution In an argon glove box, dissolve the following components in 5 mL of N-methylpyrrolidone (NMP): Sulfur-containing heterocyclic monomer: 2.0g ethyl 3,4-ethylenedioxythiophene-3-carboxylate (EDOT-ethyl ester); Comonomer: 0.5g N-vinylcaprolactam; Crosslinking agent: 0.1g tris(2-methacryloyloxyethyl) isocyanurate; First lithium salt: 0.15g lithium bis(oxalate)tetrafluoroborate (LiBF2(C2O4)); Second lithium salt: 0.05g lithium difluorophosphate (LiPO2F2); Low-temperature additive: 0.3g 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([EMIM][TFSI]).
[0044] Stir until completely dissolved to obtain a homogeneous and transparent precursor solution.
[0045] 1.5 Impregnation and photo-initiated polymerization The gradient oxide framework prepared in step 1.3 was immersed in the precursor solution from step 1.4 and allowed to stand at room temperature for 30 minutes to allow the precursor solution to fully penetrate into the pores of the oxide framework. The immersed framework was then removed, excess solution was gently absorbed from the surface with filter paper, and the framework was placed in an argon atmosphere protection chamber.
[0046] Irradiation was performed using a 365nm wavelength ultraviolet lamp with a light intensity of 30mW / cm². 2 The irradiation time was 15 minutes. Under ultraviolet light irradiation, the photoinitiator in the system (in this embodiment, the EDOT-ethyl ester monomer itself can generate free radicals to initiate polymerization under ultraviolet light irradiation, without the need for an external photoinitiator) initiates the free radical polymerization of sulfur-containing heterocyclic monomers and comonomers to form a cross-linked three-dimensional polymer network structure, which fills the pores of the oxide skeleton and forms chemical bonds with the graft layer on the surface of the oxide particles.
[0047] 1.6 Vacuum drying The photopolymerized composite membrane was placed in a vacuum oven and dried under vacuum at 60°C for 12 hours to remove residual NMP solvent, resulting in a polymer-oxide gradient composite electrolyte membrane with a thickness of approximately 30 μm.
[0048] 1.7 Performance Testing The polymer-oxide gradient composite electrolyte prepared in this embodiment was subjected to the following performance tests: (1) Ionic conductivity test: The impedance value of the electrolyte membrane was tested in a blocked electrode (stainless steel / electrolyte / stainless steel) system using the AC impedance method. The ionic conductivity was calculated according to the formula σ=L / (R×S) (where L is the membrane thickness, R is the impedance, and S is the electrode area). Tests were conducted at different temperatures (-40℃, -20℃, 0℃, 25℃, 40℃, 60℃, 80℃).
[0049] Test results: Ionic conductivity at -40℃ is 1.2×10⁻⁶ -4 S / cm, ionic conductivity at -20℃ is 3.5×10 -4 S / cm, ionic conductivity at 0℃ is 8.2×10 -4 S / cm, ionic conductivity at 25℃ is 2.5×10 -3 S / cm, ionic conductivity at 40℃ is 4.6×10 -3 S / cm, ionic conductivity at 60℃ is 8.3×10 -3 S / cm, ionic conductivity at 80℃ is 1.1×10 -2 S / cm.
[0050] (2) Lithium-ion transport number test: The constant potential polarization method combined with the AC impedance method was used to test in a Li / electrolyte / Li symmetric cell. First, the initial impedance was tested, then a constant potential of 10mV was applied, and the current change curve over time was recorded until it stabilized. Then, the impedance after stabilization was tested, and the lithium-ion transport number was calculated according to the Bruce-Vincent formula.
[0051] Test results: Lithium-ion transference number tLi + =0.65.
[0052] (3) Thermal runaway initiation temperature test: Differential scanning calorimetry (DSC) was used to heat the temperature from room temperature to 400℃ at a heating rate of 10℃ / min under an argon atmosphere. The heat flow curve was recorded and the exothermic peak initiation temperature was taken as the thermal runaway initiation temperature.
[0053] Test results: The thermal runaway initiation temperature was 235℃.
[0054] (4) Electrochemical window testing: Linear sweep voltammetry (LSV) was used in the stainless steel / electrolyte / lithium system, scanning from the open-circuit potential to 6.0V (relative to Li).+ / Li), scan rate 1mV / s, with the starting potential of a sharp current rise as the oxidative decomposition potential.
[0055] Test results: The electrochemical window is 0~4.8V (relative to Li). + / Li).
[0056] Example 2: Assembly and Performance Testing of Solid-State Batteries 2.1 Preparation of the positive electrode sheet NCM811 positive electrode active material, SuperP conductive agent, and PVDF binder were mixed in a mass ratio of 90:5:5. An appropriate amount of NMP solvent was added and stirred to form a uniform slurry. This slurry was coated onto an aluminum foil current collector and vacuum-dried at 120°C for 12 hours. After rolling, it was cut into circular sheets with a diameter of 12 mm to obtain the positive electrode sheet. The areal density of the positive electrode active material is approximately 15 mg / cm³. 2 .
[0057] 2.2 Preparation of negative electrode sheet In an argon glove box, lithium metal foil (50 μm thick) is cut into circular pieces with a diameter of 14 mm and pressed with a stainless steel roller until the thickness is uniform to obtain a negative electrode sheet.
[0058] 2.3 Setting the Interface Decoration Layer (1) Positive electrode side interface modification layer: Lithium lanthanum titanium oxide (LLTO) nanoparticles (average particle size 50 nm) were dispersed in ethanol at a concentration of 2 mg / mL, and then dropped onto the surface of the positive electrode sheet. After drying at 80 °C for 2 hours, an interface modification layer with a thickness of about 200 nm was formed.
[0059] (2) Artificial SEI layer on the negative electrode side: A layer of lithium fluoride (LiF) with a thickness of about 50 nm is deposited on the surface of the negative electrode as an artificial SEI layer.
[0060] 2.4 Battery Assembly In an argon glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), the polymer-oxide gradient composite electrolyte membrane prepared in Example 1 was cut into circular pieces with a diameter of 16 mm. These were stacked in the following order: positive electrode shell - positive electrode sheet (containing LLTO interface modification layer) - electrolyte membrane - negative electrode sheet (containing LiF artificial SEI layer) - stainless steel gasket - spring sheet - negative electrode shell. This was assembled into a CR2032 coin cell.
[0061] 2.5 Hot pressing treatment The assembled button cell is placed in a hot press and hot-pressed at 90°C and 1MPa for 1 hour to form a tight solid-solid contact between the electrolyte membrane and the positive and negative electrode plates.
[0062] 2.6 Battery Performance Test (1) Room temperature charge and discharge performance test: At 25℃, constant current charge and discharge test was performed at a rate of 0.1C (1C=180mA / g), with a voltage range of 2.8~4.3V.
[0063] Test results: The initial charge capacity was 215mAh / g, the initial discharge capacity was 185mAh / g, and the initial coulombic efficiency was 86.0%.
[0064] (2) Low temperature performance test: constant current charge and discharge test at 0.1C rate at -30℃.
[0065] Test results: The discharge capacity is 145 mAh / g, which is 78.4% of the discharge capacity at room temperature and 0.1C.
[0066] (3) Rate performance test: At 25℃, charge and discharge tests were conducted at rates of 0.1C, 0.2C, 0.5C, 1C, 2C, 3C and 5C respectively. The average value was taken after 5 cycles of each rate.
[0067] Test results: 0.1C capacity was 185mAh / g, 0.2C capacity was 178mAh / g, 0.5C capacity was 170mAh / g, 1C capacity was 163mAh / g, 2C capacity was 158mAh / g, 3C capacity was 155mAh / g, and 5C capacity was 152mAh / g. The 5C capacity retention rate was 82.2% (relative to 0.1C capacity).
[0068] (4) Low temperature cycle performance test: At -30℃, constant current charge and discharge cycle test is performed at a rate of 0.5C. The cutoff condition is that the capacity decays to less than 80% of the initial capacity or the cycle is completed for 200 cycles.
[0069] Test results: After 200 cycles, the capacity retention rate was 87.2%, which did not meet the cutoff condition.
[0070] (5) High temperature cycle performance test: At 60℃, constant current charge and discharge cycle test is performed at 1C rate. The cutoff condition is that the capacity decays to less than 80% of the initial capacity or the cycle is completed for 500 cycles.
[0071] Test results: After 500 cycles, the capacity retention rate was 92.1%, which did not meet the cutoff condition.
[0072] (6) Overcharge safety test: At 25°C, charge the battery to 10V (2.3 times the design upper limit voltage) at a constant current of 0.5C, observe whether the battery burns, explodes or other safety accidents occur, and record the thermal runaway temperature.
[0073] Test results: The battery did not burn or explode during charging to 10V. The casing temperature rose to a maximum of about 195°C, but thermal runaway was not triggered.
[0074] Example 3: Comparative Experiment of Oxide Particle Grafting Treatment This embodiment aims to illustrate the effect of grafting organic molecules onto the surface of oxide particles on interfacial impedance and ionic conductivity.
[0075] 3.1 Preparation of grafted treatment groups Based on Example 1, the oxide particles underwent surface grafting treatment before preparing the oxide coating slurry. Specifically, 0.5 g of Al-TiO2 nanoparticles and 0.8 g of La-ZrO2 microparticles were dispersed in 20 mL of anhydrous toluene, and 0.2 g of 3-mercaptopropyltrimethoxysilane (MPTMS) was added. The mixture was stirred and refluxed at 80 °C for 12 hours. After the reaction, the particles were centrifuged, washed three times with anhydrous ethanol, and vacuum dried at 60 °C to obtain mercaptosilane-grafted oxide particles. The remaining preparation steps were the same as in Example 1.
[0076] 3.2 Preparation of the ungrafted control group Based on Example 1, the surface grafting treatment step of oxide particles was omitted, and the coating slurry was prepared directly using unmodified Al-TiO2 and La-ZrO2 particles. The remaining preparation steps were the same as in Example 1.
[0077] 3.3 Performance Comparison Test The interfacial impedance of the two electrolyte membranes was tested (using a Li / electrolyte / Li symmetrical cell, the AC impedance was tested at 25℃, and the high-frequency semicircle diameter was taken as the interfacial impedance) and the ionic conductivity at 25℃ were tested respectively.
[0078] Test results: The interfacial impedance of the grafted group was 42 Ω·cm. 2 The interfacial impedance of the ungrafted control group was 87 Ω·cm. 2 Grafting treatment reduced the interfacial impedance by 51.7%. The ionic conductivity of the grafted group at 25℃ was 2.8 × 10⁻⁶. -3 S / cm, the ionic conductivity of the ungrafted control group at 25℃ was 2.2×10⁻⁶. -3 The grafting treatment increased the ionic conductivity by 27.3% (S / cm). This indicates that the organic molecular grafting layer on the surface of the oxide particles effectively reduced the oxide-polymer interfacial tension and improved the interfacial lithium-ion transport efficiency.
[0079] Example 4: Effect of different lithium salt ratios on performance This embodiment aims to illustrate the effect of different ratios of the first lithium salt (LiBF2(C2O4)) and the second lithium salt (LiPO2F2) on electrolyte performance.
[0080] 4.1 Different proportion schemes Based on Example 1, the mass ratio of the first lithium salt to the second lithium salt was changed, while the other conditions remained unchanged: Scheme A (the scheme in this embodiment): LiBF2(C2O4):LiPO2F2=3:1 (mass ratio), that is, 0.15g:0.05g; Scheme B: LiBF2(C2O4):LiPO2F2 = 4:1, i.e. 0.16g:0.04g; Scheme C: LiBF2(C2O4):LiPO2F2 = 5:1, i.e. 0.167g:0.033g; Comparative scheme D (single salt only): using only 0.20g of LiBF2(C2O4), without using LiPO2F2; Comparative scheme E (single salt only): using only 0.20g of LiPO2F2, without using LiBF2(C2O4).
[0081] 4.2 Performance Test Results
[0082] Test results show that the combined use of the two lithium salts exhibits higher ionic conductivity, lithium-ion transference number, and a wider electrochemical window compared to a single lithium salt, thanks to the synergistic effect of the two lithium salts. Among the mixed schemes, scheme A (mass ratio 3:1) has the best overall performance, and a higher proportion of lithium bis(oxalate)tetrafluoroborate is more conducive to maintaining low-temperature ionic conductivity.
[0083] Example 5: Comparative Experiment of Different Oxide Gradient Distribution Modes This embodiment aims to illustrate the performance advantages of the gradient distribution method from high content on the positive electrode side to low content on the negative electrode side in this invention compared with other distribution methods.
[0084] 5.1 Different gradient schemes Scheme F (Scheme of the present invention): Following the method of Example 1, the distribution is gradually decreasing from the positive electrode side (about 50 wt%) to the negative electrode side (about 15 wt%); Comparative scheme G (reverse gradient): The coating is performed in the reverse order of Example 1, that is, first coating slurry C (low content), then coating slurry B (intermediate), and finally coating slurry A (high content), so that the oxide content increases in a gradient from the positive electrode side to the negative electrode side (approximately 15 wt% on the positive electrode side and approximately 50 wt% on the negative electrode side). Comparison scheme H (uniform distribution): Only slurry B (intermediate content of about 35 wt%) is used for single-layer coating with a thickness of 30 μm, and the oxide content is uniformly distributed in the thickness direction.
[0085] The total oxide content and thickness of each scheme remained the same, and the other preparation conditions were the same as in Example 1.
[0086] 5.2 Performance Test Results
[0087] Test results show that scheme F (high content on the positive electrode side, low content on the negative electrode side) outperforms the comparative schemes in all performance indicators. The reverse gradient scheme G has excessively high oxide content on the negative electrode side, leading to a hardened negative electrode interface, poor contact, and a significant increase in interfacial impedance. Furthermore, the high rigidity on the negative electrode side is detrimental to suppressing lithium dendrites, resulting in the worst overall performance. The uniform distribution scheme H falls between the two in terms of performance, but it cannot simultaneously meet the differentiated requirements of high mechanical strength on the positive electrode side and low interfacial impedance on the negative electrode side. This verifies the rationality and superiority of the gradient direction design in this invention.
[0088] Example 6: Influence of process parameters on pore structure This embodiment aims to illustrate the effect of sintering temperature in step 2 on the formation of multi-level pore structure and the final electrolyte performance.
[0089] 6.1 Different sintering temperature schemes Based on Example 1, sintering temperatures of 200℃, 250℃, 300℃, 350℃, and 400℃ were used respectively, with the remaining conditions being the same as in Example 1.
[0090] 6.2 Results and Analysis
[0091] Test results show that when the sintering temperature is too low (200℃), effective neck connections fail to form between oxide particles, resulting in insufficient skeleton strength. Simultaneously, the PVB binder fails to decompose completely, and residual carbon affects ion transport. At a sintering temperature of 300℃, PVB decomposes completely, and suitable neck connections form between oxide particles, achieving optimal porosity and pore size, and maximizing ionic conductivity. When the sintering temperature is too high (400℃), oxide particles are over-sintered, causing severe pore shrinkage or even closure, reducing the amount of precursor solution impregnated, and consequently decreasing ionic conductivity. Therefore, 250–350℃ is the preferred sintering temperature range that balances pore structure and mechanical properties.
[0092] The above are merely specific embodiments of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.
Claims
1. A polymer-oxide gradient composite electrolyte, characterized in that, The electrolyte includes: A polymer matrix formed by photoinitiated polymerization of a sulfur-containing heterocyclic monomer, a comonomer, and a crosslinking agent; An oxide framework, comprising hierarchical porous oxide particles, wherein the hierarchical porous oxide particles form a gradient distribution from the positive electrode side to the negative electrode side in the electrolyte thickness direction, wherein the oxide content on the positive electrode side is 40~60wt% and the oxide content on the negative electrode side is 10~20wt%. An electrolyte salt, wherein the electrolyte salt is dispersed in the polymer matrix, and the electrolyte salt comprises a first lithium salt and a second lithium salt; Low-temperature additive, wherein the low-temperature additive is a low-melting-point ionic liquid.
2. The polymer-oxide gradient composite electrolyte according to claim 1, characterized in that, The sulfur-containing heterocyclic monomer is a 3,4-ethylenedioxythiophene derivative or a thiophene-2-carboxylic acid ester derivative, and its content in the polymer matrix is 60~80wt%; the comonomer is N-vinylcaprolactam or 2-vinylpyridine; the crosslinking agent is tris(2-methacryloyloxyethyl) isocyanurate or triallyl isocyanurate; the hierarchical porous oxide particles include nano-sized particles with a particle size of 50~200nm and micro-sized particles with a particle size of 1~5μm; the hierarchical porous oxide particles are aluminum-doped titanium dioxide or lanthanum-doped zirconium oxide.
3. The polymer-oxide gradient composite electrolyte according to claim 1, characterized in that, Organic molecules are grafted onto the surface of the oxide particles. The organic molecules contain groups that are compatible with the polymer matrix and groups that can bond to the oxide surface. The organic molecules are selected from 3-mercaptopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, or 3-isocyanopropyltriethoxysilane.
4. The polymer-oxide gradient composite electrolyte according to claim 1, characterized in that, The first lithium salt is lithium dioxatate tetrafluoroborate, and the second lithium salt is lithium difluorophosphate; the mass ratio of the first lithium salt to the second lithium salt is 3:1 to 5:1; the low-temperature additive is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide or 1-butyl-1-methylpyrrolidine bis(fluorosulfonyl)imide; the content of the low-temperature additive in the electrolyte is 5 to 15 wt%.
5. A method for preparing a polymer-oxide gradient composite electrolyte as described in any one of claims 1 to 4, characterized in that, The preparation method includes: Step 1: Disperse oxide particles in a solvent to prepare coating slurries with different oxide contents. By coating the slurries with different oxide contents one after another, a wet film with a gradient distribution of oxide content is formed on the substrate. Step 2: Dry the wet film and then sinter it at 250~350℃ to form a multi-level porous oxide framework with a gradient distribution; Step 3: Dissolve the sulfur-containing heterocyclic monomer, comonomer, crosslinking agent and electrolyte salt in an organic solvent, add a low-temperature additive, and obtain a precursor solution; Step 4: The precursor solution is immersed in the oxide skeleton obtained in Step 2, and then irradiated with ultraviolet light under an inert atmosphere to polymerize the monomers and form a polymer-oxide composite structure. Step 5: Vacuum dry the composite structure obtained in Step 4 to remove residual solvent and obtain polymer-oxide gradient composite electrolyte.
6. The preparation method according to claim 5, characterized in that, Step 1 employs a multiple coating process, followed by preliminary drying after each coating, with a coating speed of 0.1~10 cm / s; Step 2 involves sintering using a programmed temperature rise rate of 1~2℃ / min and a holding time of 2~4 hours; Step 3 uses N-methylpyrrolidone or γ-butyrolactone as the organic solvent; Step 4 uses ultraviolet light irradiation with a wavelength of 365nm and a light intensity of 10~50mW / cm². 2 The irradiation time is 5 to 30 minutes.
7. A solid-state battery, characterized in that, The solid-state battery includes a polymer-oxide gradient composite electrolyte as described in any one of claims 1 to 4, as well as a positive electrode and a negative electrode.
8. The solid-state battery according to claim 7, characterized in that, The positive electrode contains a high-nickel ternary material, lithium cobalt oxide, or lithium iron phosphate; the negative electrode is metallic lithium, lithium alloy, or silicon-carbon composite material; an interface modification layer is provided between the positive electrode and the electrolyte, the interface modification layer is composed of lithium lanthanum titanium oxide or lithium lanthanum zirconium oxide nanoparticles; an artificial SEI layer is provided between the negative electrode and the electrolyte, the artificial SEI layer is composed of lithium sulfide, lithium nitride, or lithium fluoride.
9. A method for preparing a solid-state battery as described in claim 7 or 8, characterized in that, The preparation method includes: Step 1: Mix the positive electrode active material, conductive agent, and binder in a certain proportion, coat the mixture onto the positive electrode current collector, and dry it to obtain the positive electrode sheet; Step 2: Mix the negative electrode active material, conductive agent, and binder in a certain proportion, coat the mixture onto the negative electrode current collector, and dry it to obtain the negative electrode sheet; Step 3: Place the polymer-oxide gradient composite electrolyte prepared by the method of claim 5 or 6 between the positive electrode and the negative electrode; Step 4: Hot-press at 80~100℃ to ensure tight bonding between the electrolyte and the positive and negative electrode interfaces; Step 5: Encapsulate the hot-pressed structure to obtain a solid-state battery.
10. The method for preparing a solid-state battery according to claim 9, characterized in that, The hot pressing time in step 4 is 0.5 to 2 hours.